The use of rigid gas permeable contact lens in managing severe anisometropia caused by monocular aphakia following retinal reattachment surgery and high myopia in a 13 year old girl: a case report - Tri Rahayu; Kara Citra Kalandra (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Anisometropia if not treated accordingly may cause other issues especially in developing pediatric eyes. This case is a 13 year old female presented with chief complaint of headache and double vision upon wearing prescribed spectacles. Patient had history of high myopia on both eye, amblyopia and spontaneous rhegmatogenous retinal detachment on the left eye. Retinal reattachment and lensectomy surgery were conducted to correct the problem. The surgery was performed without intra ocular lens (IOL) implantation, which left her left eye become high hyperope due to aphakia. Patient was treated with RGP CLs. Final best visual acuity with EDTRS chart was 6/48 on both eyes. Patient reported subjective visual improvement, no headache or double vision.